Comparison Of Solvent Extraction And Selective Precipitation For The Purification Of Cobalt Electrolytes At The Luilu Refinery, Drc - L. M. Roux; E. Minnaar; P. J. Cilliers; M. Bellino; R. Dye (The Southern African Institute of Mining and Metallurgy, 2007)
The classic technique to remove impurities in a cobalt stream is selective precipitation. This is usually followed by re-leaching to produce an advanced electrolyte for cobalt electrowinning. Although this technique ensures an adequate cobalt concentration in the electrowinning circuit, some of the consequences include unwanted losses through the numerous selective precipitation steps resulting in lower recoveries. One plant that currently utilizes selective precipitation is the Luilu Metallurgical Plant (Luilu) in the Democratic Republic of the Congo. This paper evaluates the benefits of using solvent extraction technology as a purification step in the Luilu Process with the aim of further increasing the overall cobalt recovery and to ensure that a suitable cobalt concentration in the advanced electrolyte is achieved. The implementation of a solvent extraction-electrowinning process is found to be beneficial in terms of achieving improved recoveries and cobalt cathode quality, however there are many other factors that impact the success of converting from the classic precipitation process used at Luilu.